PENGARUH LABA BERSIH DALAM MEMPREDIKSI ARUS KAS DIMASA MENDATANG PADA PT. UNILEVER INDONESIA TBK PERIODE 2012-2018 - Cyntia Carolina (Jurnal Ekonomi Sakti, 2021)
This study aims to provide empirical evidence regarding net income in predicting future cash flows by examining each variable. Through this research, the concept of net income can be known in predicting future cash flows. The object of research is the PT. Unilever Indonesia Tbkcompany listed on the Indonesia Stock Exchange from 2012 to 2018 which always suffered losses, did not conduct margers during the observation period, and registered successively during the observation period. The method used in object selection in this study is purposive sampling. The analysis model used in this study is a simple linear regression analysis model performed with the help of SPSS version 20 for windows computer program. The independent variable in this study is Net Income while the Dependent Variable is Cash Flow. The type of data used is secondary data.The results of this study prove that net income has a negative and significant effect in predicting future cash flows at PT. Unilever Indonesia Tbk.